The Role of Mobile Banking In Improving Service Efficiency To Customers In The Digital Era - Sulaiman Helmi; Adelia; Trisninawati; Dian Rianawati; Ratna Sesotya Wedadjati (Data : Journal of Information Systems and Management, 2024)
This paper explores the impact of Mobile Banking services, specifically the BSB Mobile application, on customer satisfaction and operational efficiency at Bank Sumsel Babel. As Mobile Banking becomes increasingly vital in the digital era, offering greater convenience and speed, this study investigates how the BSB Mobile application affects these aspects of banking service. The research aims to evaluate the effectiveness of the BSB Mobile application in enhancing customer service and reducing operational errors. It addresses a gap in existing literature by providing fresh insights into the specific challenges and benefits experienced by Bank Sumsel Babel. To achieve this, a qualitative research approach was employed, involving three months of direct observation at the Bank Sumsel Babel Tanjung Raja Sub-Branch, complemented by in-depth interviews with both staff and customers. Additionally, a thorough literature review was conducted to support the analysis. The findings reveal that the BSB Mobile application positively influences customer satisfaction by decreasing wait times and improving transaction accuracy. However, it also highlights persistent issues with network connectivity and application usability. The study concludes that while the BSB Mobile application contributes to improved customer satisfaction and operational efficiency, continuous enhancements are required to address these technical challenges. The main implication of this research is that Mobile Banking can significantly boost banking operations, provided that technological reliability and effective user training are prioritized to overcome existing limitation.